Morpho-anatomical Studies of Woodfordia fruiticosa (L.)Kurz - Kshirsagar, Anil A (Plantae Scientia, 2020)
The present investigation deals with the study of morpho-anatomical studies in node and leaf of Woodfordia fruiticosa (L.)Kurz belongs to family Lythraceae. The plant is widely used as medicinal purpose. The node has unilacunar one traced; anatomically the leaf shows several variations. The mesophyll cells are arranged loosely. The epidermis of leaf is covered with unicellular simple trichomes. The leaves are dorsiventral and hypostomatic stomata are more on lower surface of leaf. The mucilage cells are commonly occurs. The vascular bundle is bicollateral, solitary and arc shaped, parenchymatous cortex is present. These anatomical characters are useful for segregation of taxa that’s why the anatomical studies of Woodfordia were undertaken.